Assessment of mineral nutrition of cork oak through foliar analysis (Communications in Soil Science and Plant Analysis, 1996)
Abstract The changes in the mineral nutrient content of the leaves of an evergreen species, the cork oak (Quercus suber L.), were investigated to assess the possibilities of a diagnosis of the mineral nutrition of this forest species. A comprehensive pattern of change in the leaf contents of N, P, and Ca was then put forward from the data obtained. Among the time intervals that are most favorable to analyses, the end of the vegetative rest period, in January, was investigated more precisely. The variation coefficients of the leaf contents measured tree by tree were determined for a number of nutrients (N, P, K, Ca, Mg, Fe, Cu, Zn, Mn, B, Al, and Cl). The foliar analyses carried out on 7? to 10?month old leaves in stands submitted to various forest management practices led to the characterization of significant differences in P, Ca and Mn leaf contents in relation to the treatments applied.